Field notes contributed by Gerald White, fall 1984 - White, Geraldet al (1984)
Field notes contributed by Gerald White, fall 1984. A sighting by Timothy L. Dywer is also listed on the report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed